Crown‐Ether‐Like Structures Derived from a Ti8O8(Carboxylate)16 Metallacycle. Issue 2 (4th December 2013) - Artner, Christine; Czakler, Matthias; Schubert, Ulrich
Abstract Mixed‐metal clusters have been obtained from the reaction of titanium alkoxides with either strontium or lead acetate and methacrylic acid. The structures of the clusters are derived from the metallacycle Ti8O8(methacrylate)16. The Sr and Pb atoms in Sr2Ti8O8X2(OOCMe)2(methacrylate)16 (X: acetate or OiPr) and Pb2Ti8O8(OBu)2X2(methacrylate)16(BuOH)2 (X: acetate or methacrylate) occupy the central cavity of the Ti8O8 ring. In addition to the crown‐ether‐like coordination of the ring oxygen atoms to the Sr or Pb atoms, bridging carboxylate ligands support the coordination of the latter atoms. In the compound Pb2Ti6O5(OiPr)3X(methacrylate)14 (X: OiPr or methacrylate), the lead atoms are coordinated by a fragment of the Ti8O8(methacrylate)16 metallacycle.